Conflicted Memory, Irreversible Loss: Dissociative Projection in Kazuo Ishiguro’s A Pale View of Hills and Yasunari Kawabata’s The Sound of the Mountain (American & British Studies Annual, 2016)
The task of identifying main hallmarks of Ishiguro’s and Kawabata’s oeuvres is but of double-edged nature – one may be unconsciously driven to seemingly obvious and unequivocal categorisations, naming attempts at selfunderstanding and self-interpretation as the core of their narratives. Both writers are associated with highly poeticised, sensual, and atmospheric explorations of the past long gone. They thoroughly investigate and comment upon one’s personal loss, alienation, displacement, or falling into obsolescence. They depict the worlds that perished once and for all, simultaneously making them a mythologised locus of ultimate contentment, plenitude, and fulfilment. In this sense, the past is superimposable onto the present – it develops into a safe haven formed out of one’s innermost feelings and memories, a place where one takes refuge in one’s reminiscences. This paper surveys the role of memory, nostalgia, and loss in Ishiguro’s first novel, A Pale View of Hills, and Kawabata’s work from his mature period, The Sound of the Mountain. The former, a veritable attempt at recreating and re-orientalising the Orient, is subjected to a comparative analysis with the publication often assessed as the pinnacle of post-war Japanese literature. Characterial disintegration, dissociative symptoms, and affectivity that are present in both novels are analysed as determinants of their fragmentary narrative structure.
Keywords: memory studies; trauma studies; narrative identity; intertextuality; aesthetics; neo-sensualism; British literature; Japanese literature